2012
DOI: 10.1142/s201019451200308x
|View full text |Cite
|
Sign up to set email alerts
|

A Fine-Turning Copolymer Based on Triphenylamine and 3,4-Ethylenedioxythiophene via Electrochemical Polymerization

Abstract: Copolymer based on triphenylamine (TPA) and 3,4-ethylenedioxythiophene (EDOT) is polymerized electrochemically. The structure, morphology and electrochemical properties of the obtained copolymer are investigated by cyclic voltammetry and FT-IR spectroscopy. The results confirm the copolymerization of TPA/EDOT. UV-vis spectra show that the absorption peaks of the copolymer are different from those of Polytriphenylamine. Moreover, photoluminescence spectra of the copolymer exhibit great changes in emission color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…S8) which are unique for EDOT units within the structure of the copolymer. 40 Figure 6a represents the spectroelectrochemistry study and colors of P(TPAFLA-co-EDOT), where the copolymer showed distinctive spectral behaviour compared to the homopolymer. In the neutral state, the copolymer showed two absorption peaks at 374 nm and 587 nm, which corresponds to the π-π* transition polytriarylamine and PEDOT units within the polymer backbone, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…S8) which are unique for EDOT units within the structure of the copolymer. 40 Figure 6a represents the spectroelectrochemistry study and colors of P(TPAFLA-co-EDOT), where the copolymer showed distinctive spectral behaviour compared to the homopolymer. In the neutral state, the copolymer showed two absorption peaks at 374 nm and 587 nm, which corresponds to the π-π* transition polytriarylamine and PEDOT units within the polymer backbone, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…TPA–EDOT‐based copolymers were also reported by Ouyang et al and Tsuchiya et al independently via the electropolymerization and Pd‐catalyzed crosscoupling reactions of TPA and EDOT monomers, respectively. [ 44,45 ] However, their EC properties of the polymers in both reports were not studied. Hicks and co‐workers and Zhao and co‐workers both reported EDOT–TPA‐based hyper‐branched polymers in which EDOT moieties were attached to the 4‐positions of each of the three TPA phenyl rings.…”
mentioning
confidence: 99%